Tracking the reliability of force plate-derived countermovement jump metrics over time in female basketball athletes: A comparison of Principal Component Analysis vs. conventional methods - Keogh, J. A. J.; Bishop, C.; Ruder, M. C.; Kobsar, D. (Journal of Science in Sport and Exercise, 2025)
Background Establishing the reliability of countermovement jump (CMJ) metrics over multiple weeks can be important in understanding and tracking changes in jump performance over time. However, a limited number of key performance indicators are generally retained for ease of interpretation. Fortunately, CMJ metrics are often highly correlated, which offers the potential to summarize key jump aspects using principal component analysis (PCA).